농식품 수출업체의 온라인 수출 참여 및 투자의향 요인 분석 - 이두영; Douyoung Lee; 문한필; Hanpil Moon; 정대희; Daehee Chung; 김범석; Bheomseok Kim; 김상현; Sanghyun Kim (농촌경제, 2022)
본 연구는 농식품 수출업체의 온라인 수출 참여 및 디지털 기술 투자의향 요인을 분석한다. 이를 위해 295개 농식품 수출업체를 대상으로 실시한 디지털 기술 활용 실태조사를 이용하였다. 분석 결과 수입업체에 대한 판매액 비중, 신선 농식품 판매 여부, 업체 대표 연령 및 학력 수준 등 업체의 특성이 수출업체의 결정과 연관성이 있는 것으로 나타났다. 또한 디지털 기술에 대한 인식, 전망, 자기 역량 평가 등 태도 요소와 수출업체의 온라인 참여 및 투자의향 간 양의 관계가 확인되었다. 본 연구는 농식품 수출업체의 여건을 고려한 지원과 디지털 기술에 대한 인지도 향상 및 활용 역량 강화가 온라인 수출 참여 및 디지털 기술 투자 확대를 위해 중요함을 시사한다. This study investigates factors influencing agri-food exporters’ participation in online exports and investment intention in digital technology. We surveyed 295 agri-food exporters to examine their use of digital technology. The results show that the characteristics of exporters, such as the proportion of sales to importers, whether to sell fresh agri-food or not, their heads’ age and educational levels, were related to the exporters’ decision making. Also, positive relationships are found between attitudes toward digital technology (technological understanding, prospects, and self-capability evaluation), exporters' online participation, and investment intention. The key findings indicate that support customized for agri-food exporters’ conditions and enhanced understanding and utilization of digital technology are essential for their online exports and investment in digital technology.